Jacques Lacan : a feminist introduction - Grosz, Elizabeth (Routledge, 1990)
"Grosz gives a critical overview of Lacan's work from a feminist perspective. Discussing previous attempts to give a feminist reading of his work, she argues for women's autonomy based on an indifference to the Lacanian phallus." http://catdir.loc.gov/catdir/enhancements/fy0648/89011005-d.html